(untitled) (Ozone Therapy Global Journal, 2020)
Oxygen/Ozone (O2/O3) is a complementary therapy for prostate cancer, as with other types of cancer, i.e., it is used in support of conventional treatments such as radiation therapy or surgical removal of the prostate. However, some prostate cancer patients elect to manage prostate cancer by active surveillance rather than conventional therapies in accordance with treatment guidelines, or due to the uncertain prognostic value of testing and the side-effects of the treatments. The objective of this report is to demonstrate the potentially beneficial therapeutic value of O2/O3 treatment, applied in effective doses, for a prostate cancer patient electing disease management by active surveillance. The subject was a 64-year-old male diagnosed by needle biopsy with localized prostate cancer classified as being in the unfavorable intermediate risk group. He elected active surveillance to manage his cancer instead of recommended conventional therapies and received O2/O3 therapy for about a year. The treatment was divided roughly into four quarterly phases, with a PSA test performed at the end of each of the four phases. During phases 2 and 3 of the treatment, the patient’s PSA score increased from 9.7 ng/mL to 14.7 ng/mL. However, at the end of phase 4 his PSA score decreased to 11.7. During phase 4, the O2/O3 treatment was performed more regularly than during phases 2 and 3, and at lower concentrations and overall doses. This suggests that O2/O3 treatment at the correct doses and frequency of treatment may have beneficial therapeutic value for a prostate cancer patient electing disease management through active surveillance rather than conventional treatment. ..